Compact low‐loss microstrip diplexer for RF energy harvesting. Issue 8 (1st April 2017) - Bui, D.H.N.; Vuong, T.P.; Allard, B.; Verdier, J.; Benech, P.
Abstract : A compact low‐loss microstrip diplexer that forms by two band‐stop filters using interdigital capacitor and a stepped‐impedance resonator structure when joined by a miniature T ‐junction is introduced. The diplexer operates at global system for mobile communication frequency 1800 MHz and 2.45 GHz WLAN frequency which are the most available frequency bands for RF energy harvesting applications. Simulated and measured results are in very good agreement with low insertion loss of 0.4 dB and high selectivity characteristics.